Soybean isoflavones potentially prevent sarcopenia: a systematic review - Sang-Yeob Lee; Jun-Il Yoo (Journal of Ethnic Foods, 2023)
Abstract Background Soybean is an important food resource that has been used for centuries in Korean cuisine. Soybean is considered a good source of protein and a nutritional powerhouse. Isoflavone, one of the components of soybean, has been investigated for its nutritional role and physiological effects. As soybean can supply sufficient proteins for muscle and soybean isoflavone might have a direct effect on muscle, soybean could be a potential nutritional treatment for muscle atrophy. However, the effect of isoflavone on muscle atrophy is controversial. Methods Four in vitro studies and four in vivo studies were selected from the literature to determine the potential capacity of isoflavones as preventers of sarcopenia. Results In vitro and in vivo studies, there have been studies that isoflavone extracted from soybean is effective in preventing muscle atrophy. Research on soybean isoflavone and muscle loss included in this study showed that soybean isoflavone may prevent myotube atrophy by blocking the expression of MuRF1 or by regulating androgen receptors. Isoflavone has been shown to increase the diameter of myoblasts and increase muscle mass. Conclusion The present study showed the potential of soy isoflavones as a preventer of sarcopenia by preventing muscle loss.